Traumatic Subluxation of the Cervical Vertebrae in a Dog - Treatment with Surgical Stabilization: Relato de Caso - Checchinato, Daniel; Canteras Bragetto, Daniel; Espírito Santo, Jhennifer; Berbel de Lima Trinquinato, Keyla Mariana; Enjiu Okazaki, Tatiana; Anália Marinho, Larissa; Barcellos Magalhães da Rocha, Christiane Maria; Lopes Muzzi, Leonardo Augusto (Acta Scientiae Veterinariae, 2024)
Background: Trauma to the spine can lead to vertebral fracture, luxation or subluxation. Spinal injuries can cause partial or total loss of neurological functions. Neurologic signs of cervical spine injuries can range from mild pain to tetraplegia, and in cases of subluxation and instability, surgical treatment is usually indicated to stabilize the vertebrae. The aim of this study is to report the case of a dog with traumatic subluxation of the cervical spine that underwent surgical treatment to stabilize the cervical vertebrae. Case: A 7-year-old Shih-Tzu male dog, weighing 5.9 kg, was evaluated at a Veterinary Clinic with neurological signs suggestive of spinal injury. In the anamnesis, the owner reported that about 7 months ago the animal had suffered a domestic trauma, most likely due to a fall from a child’s lap. It was reported that the animal stopped walking after the fall, and initially the dog was taken to a Veterinary Clinic, where the 1st care was performed. At that time, radiographic examinations of the spine in the lumbar region and of the hip joints were performed, where no alteration was observed. Seven months after the trauma, the neurological signs still persisted, and the owner raised funds to continue the treatment. The neurological examination revealed plegia in the pelvic limbs and paresis in the forelimbs, partially preserved nociception and signs compatible with spinal injury in the cervical region. Radiographic examinations of the cervicothoracic region of the spine demonstrated possible disc protrusion between cervical vertebrae C5-C6. A computed tomography scan of the same region was performed, which showed instability and subluxation of the spine, more pronounced between the C5-C6 cervical vertebrae, promoting extradural compressive myelopathy in this medullary segment, indicating the need for surgical stabilization. The technique of ventral vertebral application of screws fixed with polymethylmethacrylate (PMMA) was performed for vertebral stabilization. Access to the ventral surface of the bodies of the C5-C6 cervical vertebrae was performed, and 6 cortical screws (1.5 mm in diameter) were implanted, with 3 screws being fixed in each cervical vertebra. Subsequently, PMMA bone cement was applied on the screws and affected vertebrae. The dog started the rehabilitation in the 2nd week after the surgical procedure. In the physiatric evaluation the patient presented with ataxia and proprioceptive deficit, absence of superficial pain and presence of deep pain in all limbs. The physiotherapy treatment protocol instituted included photobiomodulation (laser therapy), pulsatile magnetic field and kinesiotherapy. The exercises performed initially were passive, evolving to assisted, free and isometric active. Discussion: This was a lesion in the cervical region of the spine, with large vertebral bodies and with the possibility of surgical access through a ventral approach, and therefore the technique of ventral application of screws fixed with polymethylmethacrylate (PMMA) was chosen. The surgical method was chosen because of its ability to stabilize the cervical vertebrae effectively and relatively simply. The PMMA was fixed to the screws and to the vertebral bone, forming a rigid and well-shaped structure, allowing the stability of the affected cervical region. After the physiotherapy sessions, the patient showed good outcome with fast and progressive recovery of ambulation, and adequate recovery of neurological and motor function after 40 days of surgery. In conclusion, the surgical technique used, associated with physiotherapy, proved to be effective in stabilizing the cervical spine and in recovering the neurological function of the dog. Keywords: spine, cervical vertebrae, spinal injury, vertebral stabilization, canine. Título: Subluxação traumática da coluna vertebral cervical em um cão - tratamento com estabilização cirúrgica Descritores: coluna vertebral, vértebra cervical, lesão espinhal, estabilização vertebral, canino.